In vitro and in vivo pharmacological profile of OPC-61815, a water-soluble phosphate ester pro-drug of tolvaptan - Fujiki, Hiroyuki; Matsunaga, Masayuki; Furukawa, Masayuki; Yamashita, Tatsuya; Nakamura, Shigeki; Miyazaki, Toshiki; Mizuguchi, Hiroshi; Menjo, Yasuhiro; Matsuda, Takakuni; Yamada, Yoshihisa (Journal of pharmacological sciences, 2022)
Tolvaptan is an orally active vasopressin V2 receptor antagonist and used for the treatment of volume overload in some disease as an aquaretic. Tolvaptan sodium phosphate (OPC-61815) is a pro-drug of tolvaptan that was designed to improve water solubility and enable intravenous use. The conversion of OPC-61815 to tolvaptan was evaluated for in vitro and in vivo pharmacokinetic studies. The pharmacodynamics of OPC-61815 were evaluated for in vitro receptor binding affinity, in vivo aquaretic and anti-edematous action. The solubility of OPC-61815 in water at 25 °C was 72.4 mg/mL and more than 100,000 times the solubility of tolvaptan. OPC-61815 was hydrolyzed to tolvaptan by human tissue S9 fractions and main enzyme of hydrolysis was alkaline phosphatase. After intravenous administration of OPC-61815 to rats and dogs, tolvaptan was detected in plasma within 5 min and the bioavailability of tolvaptan was 57.7% and 50.9%, respectively. Binding affinity of OPC-61815 for the human V2 receptor was 1/14 weaker than that of tolvaptan. OPC-61815 exerted dose-dependent aquaretic action in rats and dogs and a corresponding anti-edematous action in rat edema models. These results suggest that OPC-61815, a water-soluble phosphate ester pro-drug of tolvaptan, is an effective aquaretic by converting to tolvaptan after intravenous administration.Tolvaptan is an orally active vasopressin V2 receptor antagonist and used for the treatment of volume overload in some disease as an aquaretic. Tolvaptan sodium phosphate (OPC-61815) is a pro-drug of tolvaptan that was designed to improve water solubility and enable intravenous use. The conversion of OPC-61815 to tolvaptan was evaluated for in vitro and in vivo pharmacokinetic studies. The pharmacodynamics of OPC-61815 were evaluated for in vitro receptor binding affinity, in vivo aquaretic and anti-edematous action. The solubility of OPC-61815 in water at 25 °C was 72.4 mg/mL and more than 100,000 times the solubility of tolvaptan. OPC-61815 was hydrolyzed to tolvaptan by human tissue S9 fractions and main enzyme of hydrolysis was alkaline phosphatase. After intravenous administration of OPC-61815 to rats and dogs, tolvaptan was detected in plasma within 5 min and the bioavailability of tolvaptan was 57.7% and 50.9%, respectively. Binding affinity of OPC-61815 for the human V2 receptor was 1/14 weaker than that of tolvaptan. OPC-61815 exerted dose-dependent aquaretic action in rats and dogs and a corresponding anti-edematous action in rat edema models. These results suggest that OPC-61815, a water-soluble phosphate ester pro-drug of tolvaptan, is an effective aquaretic by converting to tolvaptan after intravenous administration.